(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Osteoarthritis, degenerative joint disease in which the wearing down of the protective tissue at the ends of bones (cartilage) occurs gradually and worsens over time. The majority of people aged 40 years have radiographic evidence of knee osteoarthritis, is more common in women than in men.(1) Exercise has a wide range of health benefits in every individual. Mostly for middle aged population there is a clear evidence to support exercise in improving health and functional performance with well evidenced exercise programs.(2, 3) These programs have shown to improve the mobility of joints and strength of muscles around the joints by performing specific exercises for the specific muscles. This population people are often unable to undertake high intensity exercise programs. Therefore progressive resistance exercises are been used as an alternative. Many research studies have reported the benefits of resistance exercises as a physical activity for middle aged adults and individuals with limited movement. Method: The subjects in the KIMSDU campus were screened and 41 subjects fulfilling the criteria were involved. Prior consent was taken. Treatment protocol consists of progressive resistance exercises for 4 days per week for 6 weeks The interpretation of the study was done on the basis of comparing pre-test and post test assessment of Western Ontario and McMaster Universities Osteoarthritis Index(WOMAC) and BERG BALANCE TEST. Result: Intra group comparison results showed that progressive resistance exercises are effective and WOMAC and Berg Balance Test were statistically extremely significant (p<0.0001) and (p<0.0001) respectively. Conclusion: Progressive resistance exercises were significantly effective in improving the mobility and function and reducing the pain among the patients with osteoarthritis of knee.